Music as pedagogy in ELT: mechanisms, micro-sequences, and measured gains—a mini-review - Pitychoutis, Konstantinos M.; Spathopoulou, Filomachi; Scurtu, Bogdan (Frontiers in Education, 2026)
This mini-review summarises studies indexed in Scopus from 2020 to 2025, exploring how music, songs, chants, or raps serve as instructional methods for learning English. Following PRISMA guidelines, twelve studies were selected and grouped into three mechanisms: affective regulation that boosts participation; rhythmic–prosodic entrainment that enhances stress timing and intonation perception; and memory enhancement via lyric-based repetition and retrieval. Vocabulary interventions (n = 5) show consistent benefits when combined with prompted retrieval and spaced practice. Pronunciation, prosody, and speaking exercises (n = 3) are improved through techniques like singing, chanting, and rhythmic priming, with one classroom trial also improving grammar and spelling. An observational study links music perception to reading skills, viewed as contextual rather than causal evidence. Overall, research on the sustainability of these effects is limited, and intelligibility is rarely assessed with combined acoustic and perceptual methods. We recommend brief, repeatable “micro-sequences”- such as lyric-based retrieval, movement-supported rhythm activities, and caption/tempo-controlled re-listening- alongside routine delayed testing, singing-aware alignment, and equitable implementation. Overall, the evidence suggests that music is most effective in English teaching when focused on enhancing prosody and memory and fostering active participation.